(untitled) (Laisvalaikio tyrimai, 2022)
The relevance of the study of the topic is that the development of the digital economy in the context of globalization and the digital society has received great development. Globalization is the free movement of markets, capitals, people, finances, capitals, technologies, goods, services, information that develops across national borders and is the result of a multi-scale need in many industries, including automotive and aviation, mobile operating systems, retail, web servers. The purpose of the study is to analyze the development of the digital economy in the context of globalization and the digital society (on the example of China). Research objectives: 1) to reveal the directions of development of the digital economy in the context of globalization and digital society; 2) justify the development of the global economy of China as the most powerful world leader; 3) show the expansion of China’s regional influence through the development of digital technologies that contribute to the improvement of the digital society and its image. Methodology. The study of the digital society in China is based on Agile methodology and Agile philosophy as a new methodology of the digital economy, representing the methodology of complexity, as well as systemic, informational, institutional methods and approaches, which made it possible to fully represent a country like China and its development prospects . Methods of analysis and synthesis, generalization and systematization, historical and logical and comparative and axiological methods were used. The scientific novelty of the study is that the development of China’s digital economy in the context of globalization and digital society is associated with advanced innovative technologies that are just entering the forefront of historical development and show how one can become a competitive state on the world stage. China today is a large digital and industrial state, which is on the path of a market and digital economy, developing digital strategies at all levels. The mania for new economies in anticipation of a new "economic miracle" began with China, which has been growing very fast for two decades, and since 1998 at 8% annually. The lucky number 8 has become the iron law of the Chinese economy. Digital market mechanisms are a powerful microeconomic tool in China. The digital economy is based on learning, gaining the skills needed for greater deregulation, free markets, and a clear focus on short-term income generation. China’s economic development was only one part of the "economic miracle", but it is not felt by the entire population of China, most of whom feel insecure. The People’s Republic of China has a mixed economy with a three-tier enterprise system, consisting of large government companies, local hybrid and foreign firms, and small businesses. The development of the digital economy in the context of globalization and China’s digital society in the face of exponential reality and stochastic uncertainty has shown that technology is making us increasingly interconnected, dependent and vulnerable. The value of the study lies in the development of practical recommendations for improving the digital economy based on knowledge and digital technologies, within which new opportunities for society, business and the state are realized. Key words: digital economy, globalization, digital society.